Prototype traveling wave solutions of new coupled Konno-Oono equation - Kocak, Zeynep Fidan; Bulut, Hasan; Koc, Dilara Altan; Baskonus, Haci Mehmet (Elsevier Gmbh, 2016)
In this study, we apply the modified exp (-Omega (xi))-expansion function method to the new coupled Konno-Oono equation. We obtain some new travelling wave solutions such as complex function, hyperbolic function and rational function solutions. We observe that all travelling wave solutions have been verified the new coupled Konno-Oono equation by using Wolfram Mathematica 9. Then, we plot the two- and three-dimensional surfaces for all travelling wave solutions obtained in this paper by the same computer program. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: The modified exp (-Omega (xi))-expansion function method; The new coupled Konno-Oono equation; Dark soliton solution; Complex hyperbolic solution